Patient-derived tumoroids from CIC::DUX4 rearranged sarcoma identify MCL1 as a therapeutic target - Willemijn Breunis; Eva Brack; Anna C. Ehlers; Ingrid Bechtold; Samanta Kisele; Jakob Wurth; Lieke Mous; Dorita Zabele; Fabio Steffen; Felina Zahnow; Christian Britschgi; Lorenz Bankel; et al. (Nature Communications)
Abstract High-risk sarcomas, such as metastatic and relapsed Ewing and CIC-rearranged sarcoma, still have a poor prognosis despite intensive therapeutic regimens. Precision medicine approaches offer hope, and ex vivo drug response profiling of patient-derived tumor cells emerges as a promising tool to identify effective therapies for individual patients. Here, we establish ex vivo culture conditions to propagate Ewing sarcoma and CIC::DUX4 sarcoma as tumoroids. These models retain their original molecular and functional characteristics, including recurrent ARID1A mutations in CIC::DUX4 sarcoma, and serve as tumor avatars for large-scale drug testing. Screening a large drug library on a small living biobank of such tumors not only reveals distinct differences in drug response between the two entities, but also identifies a dependency of CIC::DUX4 sarcoma cells on MCL1. Mechanistically, MCL1 is identified as a direct transcriptional target of the CIC::DUX4 fusion oncogene. Genetic and pharmacological inhibition of MCL1 induces rapid apoptosis in CIC::DUX4 sarcoma cells and inhibits tumor growth in a xenograft model. Thus, MCL1 represents a potential therapeutic target for CIC::DUX4 sarcoma. Overall, our study highlights the feasibility of drug response profiling for individual sarcoma cases and suggests that further clinical assessments of its benefit are warranted.